Influence of Sei Rampah People's Market on Regional Development in Sei Rampah District of Serdang Bedagai Regency - Siregar, Mara Onggang; Sirojuzilam, Sirojuzilam; Rujiman, Rujiman (Budapest International Research and Critics University, 2021)
The objectives of this research are to: 1) Analyze the factors that affect the income of the traders of the Sei Rampah People's Market, Sei Rampah District, Serdang Bedagai Regency and 2) To analyze the impact of the Covid-19 virus pandemic on the income of traders of the Sei Rampah People's Market, Sei Rampah District, Serdang Regency Bedagai. The research was conducted in Sei Rampah District about the Effect of the Sei Rampah People's Market on Regional Development in Sei Rampah District, Serdang Bedagai Regency. The analysis method used in this research is multiple regression analysis and t test analysis. The results showed that the variable capital has a positive and significant effect on the income of the traders of the Sei Rampah People's Market in Sei Rampah District, Serdang Bedagai Regency. Meanwhile, the variables of the diversity of business premises, formal education, informal education, building renovation, and coaching have a positive but insignificant effect on the income of the Sei Rampah People's Market traders in Sei Rampah District, Serdang Bedagai Regency. The Covid 19 virus pandemic has a negative impact (change in decline) on the income of the Sei Rampah People's Market traders. This is due to a decrease in the income of the Sei Rampah People's Market traders due to the emergence of the Covid 19 virus pandemic.